A new treatment for Robert's uterus with adenomyosis: a case report and review of the literature - Yangyang Rao; Min Chen; Yiju LI (BMC, 2024)
Abstract Purpose To provide a method for the differential diagnosis of Robert's uterus with adenomyosis, a rare uterine malformation, and determine the best course of treatment. Methods A patient who had Robert's uterus with adenomyosis was admitted to our hospital in December 2022. We analyzed and summarized her case . Results Our patient complained of progressively worsening primary dysmenorrhea over the course of 3 years and lower abdominal pain lasting for 2 days. Her carbohydrate antigen 125 (CA125) level was 372.10 U/mL. Examinations conducted by several hospitals indicated that she had a single-horned uterus and a residual horned uterus, and our hospital's examination identified Robert's uterus. This malformation was corrected by open abdominal surgery. For the procedure, pelvic adhesions were first isolated, after which the closed uterine cavity and adenomyosis were resected. Subsequently, the left ovarian endometriosis cyst was resected and right tubal ligation was performed. After surgery, three injections of gonadotropin-releasing hormone A (GnRH-A) were administered, which lowered the patient's CA125 level to 14 U/mL and normalized her condition. Conclusion We pioneered a new therapeutic approach for the treatment of Robert's uterus with adenomyosis. Some valuable references are provided for clinical practice.